Narrativa autobiográfica da constituição profissional docente : as marcas de uma escola rural - Perin, Adriana Antunes (2012)
The present research investigated the way of teacher training, built on the context of rural areas, of the reality of multi-serialized classes and of the academic learning process. It objectified to reconstruct the way experienced by the author as a contribution for the field of teacher training, since by the means of the research strategy of autobiographical nature, it s possible to approach, inside its links, the processes that constitute the teaching profession and its development, and, specially, to give evidences that may challenge the standardization of a teaching system by the imposition to rural schools of a model of education produced in and to the urban area. Concerning the process of teaching constitution, based on studies such as Fontana (2010), it was aimed to figure out how and in what degree the knowledge added by academic enabled the enlargement of worldview and the development of critical sense, which in an impact with the cultural prescriptions and the influences of the milieu resulted in a specific training path. Through autobiographical narrative, three integrated stages of this process are situated: the personal constitution, the course of training and the teaching in the rural multi-seriated school. Regarding to experience in the rural school, the study was based on three references: a methodological approach between the experience in the multi-seriated and the one developed in the Bridge School of Portugal, the analysis of the nucleation process of the Brazilian multi-seriated rural schools and a claimed hegemony of the model of urban education over the rural one. In relation to the first element, it s emphasized the constitution of an environment rich in motivation, the flexibility in time for the learning consolidation, the exchange of knowledge and the mutual help among peers and family participation at school. Then the nucleation process of rural schools, at first, looked to the economic aspects and not to the need of increasing the quality of education. Such change was imposed on rural communities in the same way that the model of urban education overlaps with rural. Based on the researches, it s possible to infer that the way of teaching career is an option that requires commitment to lifelong learning and improvement. From the professional constitution take part elements of the individual s experience as a student, with cultural and academic education. Without the pretension to exhaust the themes in evidence in the study, it was signaled as ways to future jobs, the relation between the nucleation of the rural schools and the urbanization of rural areas and multi-series methodology, as a proposal of facing the challenges in nowadays serial school